THE EFFECT OF TEACHER WORK MOTIVATION OF SCHOOL ORGANIZATIONS AND LEARNING STRATEGIES ON THE EFFECTIVENESS OF VOCATIONAL SCHOOL STUDENTS' ONLINE LEARNING IN BINJAI CITY - Suryaman Amipriono; Salim Aktar (Sean Institute, 2022)
This research aims to see how much influence school organization, teacher motivation, and learning strategies have on the effectiveness of online learning of vocational students in Binjai City. This study uses descriptive verifiive methods, with the method used is survey. The data analysis techniques used are Classic Assumption Test and Path Analysis. The results of the analysis of research data showed that the influence of School Organization, Teacher Work Motivation, and Learning Strategies on the Effectiveness of Online Learning of Vocational Students in Binjai City is as follows: First, school organizations have a positive and significant effect on learning strategies. Second, teacher work motivation has a positive and significant effect on learning strategies. Third, school organizations have no positive and insignificant effect on the effectiveness of learning. Fourth, the motivation of the teacher's work has a positive and significant effect on.